2013
DOI: 10.1007/s00396-013-2903-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyampholyte microgels from colloidal salts of pectinic acid and their application as pH-responsive emulsifiers

Abstract: A novel method for obtaining cross-linked microgels of apple pectin has been introduced. This method is based on the Ugi four-component condensation in colloidal suspensions of pectinic acid and amines. Using various processing parameters (the polysaccharide concentration, the type and density of crosslink, and the optimal pH range), particles with controlled colloidal properties have been obtained. Lightly cross-linked polysaccharide chains acquire anionic character due to deprotonation of the carboxyl groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…This particular conformation in the regions of (relatively) large acid blocks would significantly affect the solubility of a fraction of the oligomeric sample with excess of MAA groups (even though it supported positive charges from IMH + and IM + ) and possibly forming regions where the hydrophilicity was substantially diminished. In agreement, it has been reported that the strong interactions between carboxyl groups in polymer chains cause the formation of thick interfacial films in oil‐in‐water emulsions at low pH values …”
Section: Resultssupporting
confidence: 87%
“…This particular conformation in the regions of (relatively) large acid blocks would significantly affect the solubility of a fraction of the oligomeric sample with excess of MAA groups (even though it supported positive charges from IMH + and IM + ) and possibly forming regions where the hydrophilicity was substantially diminished. In agreement, it has been reported that the strong interactions between carboxyl groups in polymer chains cause the formation of thick interfacial films in oil‐in‐water emulsions at low pH values …”
Section: Resultssupporting
confidence: 87%
“…In addition, responsive microgels made from surface-active hydrocolloids have potential applications in both emulsification and controlled emulsion breakdown. For instance, a pH-responsive microgel prepared from low-methoxy pectin has been reported to demonstrate substantial effectiveness for emulsion stabilization at pH 2e3, but to cause rapid destabilization of the same emulsion under alkaline conditions as a consequence of microgel layer disintegration (Mironov, Shulepov, Ponomarev, & Bakulev, 2013). Over the next few years we can confidently expect some exciting technical developments in the area of pH-responsive hydrocolloid microgels for emulsion stability and rheology control.…”
Section: Microgels: Soft Deformable Particles That Behave Like Polymersmentioning
confidence: 97%
“…In moderately concentrated emulsions, a low added concentration of non-adsorbing hydrocolloid (e.g. xanthan gum) can have an inhibiting effect on gravity-induced creaming and phase separation through the generation of a gellike viscoelastic network of depletion flocculated droplets (Moschakis, Murray, & Dickinson, 2005, 2006. Furthermore, in emulsions or foams containing substantial concentrations of nonadsorbing nanoparticles, the ordering of the particle layers in thin films between droplets or bubbles can produce a kinetic structural barrier providing enhanced stability with respect to coagulation or coalescence (Dickinson, 2015a;Wasan, Nikolov, & Aimetti, 2004).…”
Section: Mechanisms Of Stabilization and Destabilization: Particles Vmentioning
confidence: 99%
“…Microgels can be obtained by either chemical or physical cross-linkage methods. Our research group elaborated the approach for synthesis of cross-linked polysaccharide microgels via the Ugi multicomponent condensation (U-4CR) in diluted colloidal suspensions (at polysaccharide concentrations below the critical concentration of chain entanglement) [2].…”
Section: Extended Abstractmentioning
confidence: 99%
“…Microgels can be obtained by either chemical or physical cross-linkage methods. Our research group elaborated the approach for synthesis of cross-linked polysaccharide microgels via the Ugi multicomponent condensation (U-4CR) in diluted colloidal suspensions (at polysaccharide concentrations below the critical concentration of chain entanglement) [2].The objective of this research was to develop the new range of microgels suitable for drug delivery application. Modified pectin comprising hydrazyde groups has been chosen as a polymeric network according to its biocompatibility, biodegradability, high mucoadhesiveness, and possession of both acidic and basic functional groups.…”
mentioning
confidence: 99%